Methods for assessing 3D virtual worlds in design education - Gül, L.; Kim, M.; Gu, N.; Wang, Xiangyu (2014)
With the advancement and increasing adoption of information and communication technologies, 3D virtual worlds, being a part of these revolutionary forces, have the potential to make a major contribution to design education as a new teaching and learning environment. Considering this changing trend, we have been employing 3D virtual worlds in the design curriculum over the past decade. To critically understand the impact of the technologies on design education, this chapter explores and demonstrates three different assessment methods of 3D virtual worlds in design education, through three case studies. The chapter also concludes with insights into the applications of virtual environments in collaborative design teaching.